Transcriptomic Analysis of the Adaptation of Listeria monocytogenes to Lagoon and Soil Matrices Associated with a Piggery Environment: Comparison of Expression Profiles - Vivant, Anne-Laure; Desneux, Jeremy; Pourcher, Anne-Marie; Piveteau, Pascal (Frontiers in Microbiology, 2017)
Understanding how Listeria monocytogenes, the causative agent of listeriosis, adapts to the environment is crucial. Adaptation to new matrices requires regulation of gene expression. To determine how the pathogen adapts to lagoon effluent and soil, two matrices where L. monocytogenes has been isolated, we compared the transcriptomes of L. monocytogenes CIP 110868 twenty minutes and twenty-four hours after its transfer to effluent and soil extract. Results showed major variations in the transcriptome of L. monocytogenes in the lagoon effluent but only minor modifications in the soil. In both the lagoon effluent and in the soil, genes involved in mobility and chemotaxis and in the transport of carbohydrates were the most frequently represented in the set of genes with higher transcript levels, and genes with phage-related functions were the most represented in the set of genes with lower transcript levels. A modification of the cell envelop was only found in the lagoon environment. Finally, the differential analysis included a large proportion of regulators, regulons and ncRNAs.